Determination of Healthcare Professionals' Knowledge of Fever Management - Şaduman Dinçer; Fatma Taş Arslan (Galenos Yayinevi, 2017)
Introduction: This study aimed to determinate health professionals' knowledge of fever management and antipyretics use. Methods: This study was performed in 160 healthcare professionals from pediatric clinics in three hospitals. A questionnaire form was developed according to current literature. Descriptive statistics, the Mann-Whitney U test, and Kruskal-Wallis test were used. Results: 83.1% of participant were women, 42.5% had bachelor degree, 35.0% had at least 10 years experience as a nurse in general, and 55% had at least 3 years experience in pediatric clinics. It was found that 86.9% of them did not have any education after graduation about fever management, 73.8% of them did not read scientific articles about fever management. More than half of the participants (50.6%) found themselves having sufficient knowledge about fever management. The mean knowledge of physiology of fever score was found to be 5.78±1.06. The mean general knowledge of fever management score was 5.07±1.03. The mean, antipyretic use in fevel management knowledge score was 4.17±0.87, and the total score was 15.02±1.90. Fever management knowledge score in health professionals, who had master degree and those who have worked in pediatric clinics for 0-2 years, was found to be higher than the others (p=0.049 and p=0.041, respectively). There was no significant difference in fever management knowledge score, socio-demographic characteristics, and professional status between the participants. Conclusion: Although there were some insufficiency in some domains of fever management the level of knowledge of healthcare professionals was found to be high. Standardization of clinical practice for pediatric fever management and education of healthcare professionals are of great importance.